(untitled) - Bronson, Gary J. (Pacific Grove, Calif., 1999)
The Second Edition of Gary Bronson's highly successful book takes a hands-on, applications approach to CS1. The book begins with procedural programming in C, and then gradually introduces object-oriented programming features and the C++ language syntax that enables first-time programmers to use them.
Keywords: C++ (Computer program language),C++ (Ngôn ngữ chương trình máy tính)